2013
DOI: 10.1155/2013/741740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Symptom Recovery on a Gluten-Free Diet in Canadian Adults with Celiac Disease

Abstract: Delays in diagnosis of celiac disease in Canada remain unacceptably long despite wider availability of serological screening tests. Many patients report continuing symptoms despite adhering to a gluten-free diet for >5 years, with women experiencing more symptoms and a lower recovery rate than men. Awareness of celiac disease needs improvement, and follow-up with a physician and a dietitian is essential for all patients with celiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 51 publications
3
44
2
Order By: Relevance
“…More recently, a large questionnaire study of 5912 Canadian celiac patients has suggested that ''extreme weakness/tiredness'' is reported by patients to improve over a prolonged period on GFD, such that of those on GFD for more than five years 72.4% reported this symptom had recovered. 95 Interpretation of these findings is made more difficult by the fact that data originate from cross-sectional studies, rather than from either randomized controlled trials of the effect of GFD, or cohort studies to permit examination of the alteration in state within individuals after establishment of a diet. It is therefore unwise to conclude too firmly that GFD either does or does not alleviate fatigue in CD from the available evidence.…”
Section: Fatiguementioning
confidence: 99%
“…More recently, a large questionnaire study of 5912 Canadian celiac patients has suggested that ''extreme weakness/tiredness'' is reported by patients to improve over a prolonged period on GFD, such that of those on GFD for more than five years 72.4% reported this symptom had recovered. 95 Interpretation of these findings is made more difficult by the fact that data originate from cross-sectional studies, rather than from either randomized controlled trials of the effect of GFD, or cohort studies to permit examination of the alteration in state within individuals after establishment of a diet. It is therefore unwise to conclude too firmly that GFD either does or does not alleviate fatigue in CD from the available evidence.…”
Section: Fatiguementioning
confidence: 99%
“…In children identified via screening there is increasing evidence that growth and bone quality can be adversely affected (15,19). Because the complaints of celiac disease are so nonspecific, it often takes years before symptomatic patients are diagnosed (20). By then, symptoms and organic complications of celiac disease that has remained untreated for many years, such as pancreatic failure or atrophy of the spleen, are often no longer reversible (20)(21)(22).…”
mentioning
confidence: 99%
“…In this study, the total quality of life score of celiac patients who always followed a gluten-free diet were significantly higher than patients who sometimes followed the diet (Table 3). In a study evaluating the effect of time of adherence to gluten-free diet on health-related quality of life scores, individuals whose compliance to the diet was longer than 5 years have significantly higher quality of life scores than those whose compliance was less than 1 year (Pulido et al, 2013). In this study, the same time criteria had similar effects on total quality of life scores.…”
Section: Resultsmentioning
confidence: 55%